Linguistic minorities in Portugal: the Barranquenho - Banza, Ana Paula (2021)
Barrancos is a small Alentejo village located in the south of Portugal, on the border with Spain, currently with less than 2000 inhabitants. As a result of particular geographical and historical circumstances, the Barranquenho, spoken by the whole community of Barrancos, is currently recognized by many experts as a mixed language, resulting from the contact between southern Portuguese and southern Castilian. This originality distinguishes it from all the varieties of Portuguese and also from Mirandese, a variety of Asturo-Leonese spoken in Portuguese territory which has already been recognized since 1999 as an official regional language. Thus, the present paper means to present a general, but up-to-date, view of the most important characteristics and struggles of the Barranquenho minority, in relation to the Mirandese, and of the policies regarding these linguistic minorities in Portugal, as a safeguard guarantee of this intangible heritage.